2019
DOI: 10.4103/jos.jos_58_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leptin concentration in Gingival Crevicular Fluid (GCF) during orthodontic tooth movement and its correlation to the rate of tooth movement

Abstract: OBJECTIVES: Leptin, a polypeptide which is related to body fat regulation, is also found to have a role in the inflammatory reaction. The aim of this study is to assess the concentration of leptin in Gingival Crevicular Fluid (GCF) during orthodontic force application and to correlate its concentration to rate of tooth movement. METHODS: Twenty orthodontic patients (10 males and 10 females) were selected for the study. Leptin concentration was measured at T0, before for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This was followed by a decrease, which ended after one month below the initial concentration. Furthermore, a clear positive correlation was observed between leptin concentration in the sulcus fluid and speed of tooth movement [30]. This could be one reason why faster tooth movement is observed in overweight children and adolescents [31].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This was followed by a decrease, which ended after one month below the initial concentration. Furthermore, a clear positive correlation was observed between leptin concentration in the sulcus fluid and speed of tooth movement [30]. This could be one reason why faster tooth movement is observed in overweight children and adolescents [31].…”
Section: Introductionmentioning
confidence: 83%
“…Bone remodelling is essential for orthodontic tooth movement. With this in mind, the concentration of leptin in the sulcus fluid during orthodontic treatment has already been investigated [29,30]. An increase in leptin concentration was observed during the first phase of tooth movement.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to demonstrate that leptin can directly interact with cementoblasts and influence their biological response to compressive forces. Clinical studies have described that the levels of leptin present in crevicular fluid drastically vary during orthodontically induced tooth movement, suggesting that leptin-leptin receptor interactions could play a biological role on this process [ 18 , 19 ]. Immunohistological analysis performed on primates has shown that leptin receptors are widely expressed in the junctional epithelium and in mineralizing areas of the periodontal ligament [ 20 ], as well as it has been demonstrated that the gingiva can directly release soluble leptin receptors into crevicular fluid [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that manipulating food is more difficult (68) and total food consumption might be lower (67) compared to children without wearing a dental brace. One previous study has reported mean body weight to significantly decrease during orthodontic treatment (from pre-treatment to 1 month into treatment), predominantly due to discomfort, however the study was of a limited size (n = 30) and in adults rather than children (66) Furthermore, a previous study found that increasing leptinlevels were reported in adults with orthodontic appliances, which might also lead to lower appetite and therefore to reduced food intake (69) and might contribute to a reduced BMI. In this context previous orthodontic research has found that adolescents with obesity had an increased initial tooth displacement and a higher rate of tooth movement compared to a normal-weight group, and it has been proposed that this may affect the treatment period (70)(71)(72), and therefore it is perhaps unsurprising that we found a difference in BMI related to wearing a dental brace.…”
Section: Weight Status and Covariatesmentioning
confidence: 98%